Automating the Manufacturing Process: Feature Recognition and CNC Programming with Siemens NX - Iulian Stanasel; Caius Stanasel (Engineering Research: Perspectives on Recent Advances Vol. 3, 2025)
In the context of fierce market competition, companies are forced to continuously optimize their product portfolios, both in terms of design and functional performance and by adopting advanced manufacturing technologies. This requirement is aimed at achieving high-performance standards while reducing production costs and time. The close integration of CAD and CAM applications has driven research in the field of geometric entity recognition (Feature Based Modeling - FBM), with the aim of automating various stages of the product life cycle, from design and manufacturing to production planning, assembly and quality management. To make the production process more efficient, an important research direction is the automatic generation of machining programs and Computer Numerical Control (CNC) machine tools, directly from the characteristics of the constituent geometric entities of the part. Through a case study, this paper explores the methodology for generating CNC machining programs using the entity recognition (FBM) functionalities offered by the Siemens NX platform. Using feature-based Machining (FBM) reduced the creation time of the CNC program from 47 minutes using traditional methods in Siemens NX CAM to only 18 minutes. Also, Feature Based Machining automates processes and eliminates repetitive tasks, optimizing the entire manufacturing process, ensuring high consistency, and minimizing human error.